Decision-making in the purchase of equipment in agricultural research laboratories: a multiple-criteria approach under partial information - Moreno Rodriguez, Jenny Milena; Abreu Kang, Takanni Hannaka; Asfora Frej, Eduarda; Teixeira de Almeida, Adiel (Growing Science in Canada, 2024)
Investments in the agricultural sector represented by innovations and new technologies strongly influence the economic growth in developing countries. In this context, purchasing decisions have become more relevant. Multiple-criteria decision-making techniques are well suited for decision-makers (DMs) who are considering the introduction of new technologies. In this paper, a multi-criteria model is built to help a Colombian agricultural research company make decisions on purchasing different laboratory equipment. A compensatory approach based on trade-offs is used to elicit the preferences of a group of DMs. The high number of answers and cognitive effort required from them during the elicitation process led to using an alternative approach based on partial information, called the FITradeoff (The Flexible and Interactive Tradeoff) method. It showed to be the best fit to solve the company’s purchasing problem and allowed its managers to make decisions that consider criteria other than price, taking account of the DMs’ conflicting viewpoints. The proposed model aimed at contributing to the articulation of the end-user knowledge in decision-making in order to ensure effective articulation of actors and strengthening of science, technology and innovation in agriculture.